MARKOV CHAIN ANALYSIS: UNDERSTANDING CHANGES IN CONSUMER INTEREST IN PURCHASING FOOD TYPES AS AN INITIAL STEP IN CULINARY BUSINESS DECISIONS - Bekti Nugrahadi; Anita Oktaviana Trisna Devi; Agung Widiyanto Fajar Sutrisno; Yunita Primasanti; Nasyita Vivi Amalia (Jurnal Disprotek, 2026)
Indonesia features a diverse culinary landscape characterized by regional variations in ingredients, processing methods, and flavors. The culinary industry is expanding rapidly, with the creative economy making a substantial contribution to national GDP. Effective planning is essential for continued industry success. This study analyzed shifts in consumer interest in food selection as an initial step in culinary business decision-making. Markov analysis was employed to predict customer preferences, forecast future market trends, and calculate transition probability matrices and steady-state distributions. Analysis of data from 40 respondents indicated a significant shift in consumer preferences. Interest in heavy food menus, including chicken, duck, and seafood, declined substantially, approaching 0%. In contrast, cold drinks demonstrated continued growth and remained the dominant category at steady-state, accounting for 32.22%. These findings suggest that long-term consumption trends are likely to favor cold drinks, providing valuable insights for culinary entrepreneurs. ANALISIS RANTAI MARKOV UNTUK MENGETAHUI PERUBAHAN MINAT KONSUMEN DALAM PEMILIHAN JENIS MAKANAN SEBAGAI LANGKAH AWAL KEPUTUSAN BISNIS KULINERIndonesia memiliki kuliner yang beragam, terdapat banyak perbedaan dari setiap daerah dari segi bahan, cara pengolahan dan cita rasa. Industri kuliner saat ini berkembang sangat pesat dan merupakan sektor ekonomi kreatif yang berkontribusi signifikan terhadap PDB. Kesuksesan suatu usaha industri kuliner sangat bergantung pada perencanaan yang baik. Tujuan dari penelitian ini untuk menganalisis perubahan minat konsumen dalam pemilihan jenis makanan sebagai langkah awal pengambilan keputusan bisnis kuliner, Menggunakan pendekatan analisis Markov untuk memprediksi preferensi pelanggan dan tren pasar di masa yang akan datang. Serta menghitung matriks probabilitas transisis dan distribusi steady-state. Berdasarkan 40 orang responden, perhitungan menunjukkan pola perpindahan minat konsumen signifikan. Menu makanan berat seperti ayam dan bebek serta seafood cenderung mengalami penuruan minat mendekati 0%. Di sisi lain, minuman dingin menunjukkan persentase yang terus meningkat dan bertahan sebagai kategori dominan pada kondisi steady-state yaitu sebesar 32,22%. Hasil perhitungan tersebut memberikan pandangan bagi pelaku usaha kuliner bahwa tren konsumsi jangka panjang cenderung mengarah pada produk minuman dingin.